Aplicación de un sistema electro-fenton con un ánodo de sacrificio de acero y un cátodo de difusión de gas como alternativa para la remoción de contaminantes de preocupación emergente (2020)
The appearance of pharmaceutical compounds both in hospital waters and in the effluents of wastewater treatment plants, and the great potential problems in the environment and in human health that this can generate, has led to the need to propose complementary treatments, mainly tertiaries that are capable of efficiently removing this type of micro-contaminants. Among these treatments, systems based on the Fenton reaction (a type of advanced oxidation process) have been evaluated, which has proven to be efficient in removing a wide variety of contaminants. In this work, the use of an electro-Fenton system was proposed, in which the iron and hydrogen peroxide species, necessary reagents in the Fenton reaction, are electrogenerated. In the first case, from a recycled stainless-steel sacrificial anode (austenitic type - AISI 420 - from a recyclable residue), and in the case of hydrogen peroxide, using a gas diffusion cathode (with fiber of graphite). The system was worked in the presence of citric acid at near-neutral pH value. The results show that when the current density of 0.31 mA/cm2 was applied on the anode, a concentration of 0.07 mM of iron species was generated after 5 minutes, which increases progressively until a maximum of ~ 0.18 mM after 60 min. Initial results showed that electro-generated iron species, in combination with 0.40 mM hydrogen peroxide, was also electro-generated; leads to the complete degradation of ciprofloxacin, CIP (a model compound of contaminants of emerging concern), therefore its antimicrobial activity is expected to decrease as well. Taking into account degradation data (from other authors) of ciprofloxacin using similar electro-Fenton systems, and degradation products detected during treatment, in silico calculations of ThOD, Log P and molecular coupling “Docking” were performed to determine biodegradability and toxicity, both of the original compound (CIP) and the degradation products. The calculations show a tendency to increase the degradability of the intermediates formed and to decrease both toxicity and antimicrobial capacity due to low enzyme inhibition values. Electro-Fenton systems have proven to be efficient in removing this type of compound and tend to be a sustainable system with low energy consumption, when alternatives are used in their implementation, such as the one demonstrated in this work, by using reuse materials.